Debut of Gastroesophageal Reflux Concomitant with Administration of Sublingual Immunotherapy - Jacob Juel (Case Reports in Gastrointestinal Medicine)
Gastroesophageal reflux disease (GORD) is an often debilitating condition characterised by retrograde flow of content from stomach into the oesophagus, where the low pH of the stomach acid irritates the mucosa of the oesophagus. The most dominant symptoms in GORD are pyrosis, regurgitation, and dysphagia. Sublingual immunotherapy (SLIT) was first described in 1986. Following this description, the use has greatly increased in the treatment of allergic rhinitis, as an alternative to subcutaneously administered immunotherapy. Side effects are commonly of oropharyngeal and gastrointestinal nature, for example, swelling, itching, irritation, ulceration of the oropharynx and nausea, abdominal pain, vomiting, and diarrhoea. More serious side effects are dominated by respiratory tract and systemic manifestations. A 30-year-old male experienced refractory, relentless, and debilitation GORD subsequent to administration of sublingual immunotherapy for house dust mite in allergic rhinitis. The patient had to stop the SLIT after two weeks of administration due to GORD. The cessation resulted in rapid resolution of symptoms.